Application Of Solar Panels As A Source Of Electricity For Hydroponic Irrigation Systems - David P. Rumambi; Daniel P.M. Ludong; Alden M. Saiya; Frangky Paat (Jurnal Agroekoteknologi Terapan, 2023)
The aim of this research is to design an eletrtic circuit system using solar panel to meet the needs of electric pumps of hydroponic irrigation system. This research may develop the knowledge that applied to application of solar panel system and to modify hydroponic planting systems by using solar panels to regulate the air circulation in plants. This study used an experimental method which conducts in Kelurahan Nyiur 1, at Wenang village. The data was obtained and analyzed descriptively. The results of the application of solar panels as a source of electricity for the system consist of several main components, namely the charger controller, relay, power supply, ats initial dc laptop, timer controller and 12 volt dc water pump. The result shows that solar panel application as an electric source of hydroponic system works well and so does the works of timer controller as water pump controller. Keywords: Solar panels, charger controller, Hydroponics, Deep Flow Technique Abstrak Tujuan penelitian ini adalah mendesain sistem rangkaian listrik menggunakan panel surya untuk kebutuhan listrik pompa irigasi sistem hidroponik. Manfaat penelitian ini yaitu mengembangkan ilmu pengetahuan yang diterapkan pada aplikasi sistem panel surya dan memodifikasi sistem tanam hidroponik menggunakan panel surya agar sirkulasi air pada tanaman bisa terkontrol. Penelitian ini mengunakan metode eksperimental yang dilaksanakan di Kecamatan Wenang Kelurahan Nyiur Lingkungan 1 dimana data yang didapat dianalisis secara deskriptif. Hasil aplikasi panel surya sebagai sumber listrik sistem terdiri dari beberapa komponen utama yaitu charger controller, relay, power supply, ats dc awallaptop, timer controller dan pompa air dc 12 volt. Hasil penelitian menunjukan aplikasi panel surya sebagai sumber listrik sistem hidroponik dan cara kerja timer controller sebagai pengontrol pompa air, dapat bekerja dengan baik. Kata kunci: Panel surya, charger controller, Hidroponik, Deep Flow Technique